Pembelajaran Sejarah Sebagai Upaya Pengembangan Kesadaran Sejarah Bangsa melalui Pendidikan Karakter Pancasila - Margaretha Taniria Sarumaha; Sariyatun Sariyatun; Susanto Susanto (Universitas Sebelas Maret, 2022)
This study aims to provide an effort in developing students' national history awareness, through Pancasila character education in history learning. This is because history learning has a very important position in the world of education because the values contained are the most important aspects in the development of national identity. When this young generation becomes the holder of the main and supporting roles in carrying out the life of the nation, the character that has been formed in them becomes strong foundation in carrying out this role. The approach used in this research is a library research approach. This approach is carried out by examining theories, concepts and principles related to the discussion. Meanwhile, data collection was carried out using document study techniques, namely data obtained from the relevant literature. The data were analyzed by qualitative descriptive analysis, in which all the collected data will be analyzed systematically. The results of the study indicate that history learning has a responsibility in continuing culture, playing an active role in the era of globalization and the development of science and technology. The development of the global market in the era of globalization is a challenge for historical education, by growing awareness of the history of a nation through Pancasila character education as an effort to prepare the Golden Generation.